1998
DOI: 10.1016/s0014-5793(98)00975-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of acidic pH on OmpC porin: wild‐type and mutant studies

Abstract: By use of the patch clamp technique, we have compared the electrophysiological signature of OmpC porin channels at neutral and acidic pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Finally, it is also important to consider whether the sensitivity of the mutant to acidic pH is due to the inability of this porin mutant to close at low pH. There have been numerous reports that acidic pH triggers closure of wild-type porins in electrophysiological experiments (25,35,42,43). We have confirmed this mode of porin regulation in vivo by comparing the flux of cephaloridine at pH 3.6 with that at pH 6.0 (in the absence of added polyamines).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, it is also important to consider whether the sensitivity of the mutant to acidic pH is due to the inability of this porin mutant to close at low pH. There have been numerous reports that acidic pH triggers closure of wild-type porins in electrophysiological experiments (25,35,42,43). We have confirmed this mode of porin regulation in vivo by comparing the flux of cephaloridine at pH 3.6 with that at pH 6.0 (in the absence of added polyamines).…”
Section: Resultssupporting
confidence: 61%
“…It is noteworthy that cells reduce their outer membrane permeability under acidic conditions by the use of multiple pathways that may act sequentially. The pH-induced closure of porins is immediate (25,35,42) and will rapidly lead to about a 20 to 25% reduction in permeability. This reduction is followed by the slower processes of regulation of gene expression, which affects the porin regulon and the cad operon.…”
Section: Resultsmentioning
confidence: 99%
“…This may either indicate pH gating of the Rv1698 channel or a proton-induced conformational change of the constriction zone that causes a decreased conductivity for Tris-HCl. Both mechanisms were observed for porins of Gram-negative bacteria (33,34).…”
Section: Ion Selectivity Of the Rv1698mentioning
confidence: 90%
“…17 Experiments performed on another E. coli porin OmpC revealed that acidic pH stabilizes the porin in a closed state without affecting the single channel conductance. 18 OmpG, a monomeric porin of E. coli also displayed pH induced modulation in acidic conditions, with an increased frequency of the single step transition between the open and the closed state. 19 The properties of TolC, a unique trimeric protein with an outer membrane b-barrel core and a a-helical periplasmic tunnel domain, 20 have also been investigated at various pH's, and acidic pH was found to cause a decrease in channel conductance.…”
Section: Introductionmentioning
confidence: 99%